Dollar Cost Averaging: An Effective Investment Strategy - Hussain, Muzzakir (2006)
Dollar cost averaging is a highly controversial investment strategy, which has lately gained popularity in midst of the debate. While it is increasingly recommended by scores of investment advisors, as an effective strategy; many academics argue that this strategy merely reduces risk, at the cost of the opportunity to earn higher returns. In addition, the increased popularity of the strategy amongst individual investors, have lead to claims, that it a product of irrational behaviour of investors. This dissertation will explore whether Dollar Cost Averaging is irrationality or an effective investment strategy for investors of all types with different risk tolerance levels.